PERSEPSI KUALITAS LAYANAN DAN KEDEKATAN EMOSIONAL TERHADAP KEPUASAN MASYARAKAT PADA PELAYANAN PUSKESMAS KECAMATAN MOYO HILIR - Rachman, Rosyidah; Ariyani, Indri (Samalewa: Jurnal Riset & Kajian Manajemen, 2024)
This study aims to examine perceptions of service quality and emotional closeness on community satisfaction at Moyo Hilir Health Centre services. The type of this study was associative study which aims to examine the effect of perceived service quality (X1) and emotional closeness (X2) on community satisfaction at Moyo Hilir Health Centre services (Y). products among students at Samawa University, Sumbawa Besar. The type of data used in this study was quantitative data obtained directly from research respondents using a questionnaire. The respondents in this study were 55 people who used the Moyo Hilir Health Center services in the period November 2022 who were determined using probability sampling techniques with the simple random sampling method. The data used in this study were processed with SPSS software for analysis using multiple linear regression analysis techniques, partial hypothesis testing (t test), simultaneous hypothesis testing (F test), and determinant coefficient testing (R2). The results of this study showed that service quality (X1) and emotional closeness (X2) had a positive and significant effect on community satisfaction at Moyo Hilir Health Centre services (Y), both partially and simultaneously. The effect of service quality and emotional closeness on community satisfaction at Moyo Hilir Health Center services was 75.6%, while the remaining of 24.4% was effected by other factors not included in this study, such as product quality, price or costs, and ease of obtaining products or services.